Productivity and Seasonal Index of Anchovy (Stolephorus sp) Fishing on Bagan Boat Fishing Gear at UPTD Regional Fisheries Port I (PPW1) Carocok Tarusan, West Sumatra - Lestari, Mega; Brown, Arthur; Zain, Jonny (Jurnal Perikanan dan Kelautan, 2025)
Productivity and estimation of fishing season index in marine areas are very much needed to facilitate fishermen's fishing operations, so they are practical and efficient. This research was conducted from February 28, 2024, to March 9, 2024. This research was conducted at the UPTD Fishing Port Region I (PPW1), Carocok Tarusan, West Sumatra Province. This study aimed to calculate fishing productivity and the fishing season index of anchovies (Stolephorus sp) at the UPTD Fishing Port Region I (PPW1), Carocok Tarusan, West Sumatra Province. This research is based on a survey method involving observations and collecting primary and secondary data directly at the UPTD Fishing Port Region I (PPW1), Carocok Tarusan, West Sumatra Province. The highest CPUE value of anchovies occurred in 2021, 142.66 kg/ship. The lowest CPUE occurred in 2019, at 73.30 kg/boats. The peak season for anchovy landings at PPW1 Carocok was identified to occur from April to August, as indicated by an IMP value of more than 100%. The moderate season for anchovy landings was shown to occur from January to March and September to December, as indicated by an IMP value of more than 50%. No month was identified as a lean season where the IMP value was less than 50%.